Non-AIDS Events in Individuals With Spontaneous Control of HIV-1: A Systematic Review - Groenendijk, Albert L; Vos, Wilhelm A J W; Dos Santos, Jéssica C; Rokx, Casper; van der Ven, Andre J A M; Verbon, Annelies (Journal of acquired immune deficiency syndromes (1999), 2022)
Despite antiretroviral therapy (ART), people living with HIV (PLHIV) are at increased risk for non-AIDS-defining events (nADEs), including cardiovascular events, non-AIDS malignances, hepatic disease, and bacterial pneumonia.BACKGROUNDDespite antiretroviral therapy (ART), people living with HIV (PLHIV) are at increased risk for non-AIDS-defining events (nADEs), including cardiovascular events, non-AIDS malignances, hepatic disease, and bacterial pneumonia.This systematic review seeks to answer the question: are PLHIV who spontaneously control HIV-1 subject to an increased risk of various nADEs relative to noncontrolling PLHIV on ART and people without HIV?SETTINGThis systematic review seeks to answer the question: are PLHIV who spontaneously control HIV-1 subject to an increased risk of various nADEs relative to noncontrolling PLHIV on ART and people without HIV?Databases were searched on June 9, 2021 with a search syntax focused on the elements "HIV," "spontaneous control," and "clinical outcomes": Embase.com (includes Embase and Medline), Medline Ovid (includes PubMed), Cochrane library, Web of Science, and Google Scholar. Included were studies reporting non-AIDS events in spontaneous controllers. Excluded were case reports, conference papers, editorials, and reviews.METHODSDatabases were searched on June 9, 2021 with a search syntax focused on the elements "HIV," "spontaneous control," and "clinical outcomes": Embase.com (includes Embase and Medline), Medline Ovid (includes PubMed), Cochrane library, Web of Science, and Google Scholar. Included were studies reporting non-AIDS events in spontaneous controllers. Excluded were case reports, conference papers, editorials, and reviews.Of 1134 identified records, 34 were assessed for full-text and 12 studies were included in the qualitative synthesis: 5 cohorts, 2 cross-sectional prevalence studies, 4 cross-sectional imaging studies, and one case series. Four of 5 cohort studies showed that spontaneous controllers have a similar risk to develop nADEs compared with PLHIV on suppressive ART, specifically cardiovascular events, non-AIDS malignancies, hepatic disease, and bacterial pneumonia. Cross-sectional imaging studies showed a higher presence of subclinical cardiovascular disease in spontaneous controllers, than in people without HIV.RESULTSOf 1134 identified records, 34 were assessed for full-text and 12 studies were included in the qualitative synthesis: 5 cohorts, 2 cross-sectional prevalence studies, 4 cross-sectional imaging studies, and one case series. Four of 5 cohort studies showed that spontaneous controllers have a similar risk to develop nADEs compared with PLHIV on suppressive ART, specifically cardiovascular events, non-AIDS malignancies, hepatic disease, and bacterial pneumonia. Cross-sectional imaging studies showed a higher presence of subclinical cardiovascular disease in spontaneous controllers, than in people without HIV.Individuals with spontaneous control of HIV-1 do not seem to be at a greater risk to develop different nADEs compared with PLHIV on suppressive ART. More data are needed, because the present conclusions are based on a limited number of studies that show large heterogeneity among them.CONCLUSIONIndividuals with spontaneous control of HIV-1 do not seem to be at a greater risk to develop different nADEs compared with PLHIV on suppressive ART. More data are needed, because the present conclusions are based on a limited number of studies that show large heterogeneity among them.